Urban Agriculture: A Solution to Land Constraints Amidst Urbanization - Kurnianto, Bambang Tri (Westscience Press, 2024)
Urban agriculture is emerging as a critical strategy for addressing the challenges posed by rapid urbanization and land scarcity. As cities expand, the demand for food production increases, necessitating innovative solutions to ensure food security and sustainability. This article explores the potential of urban agriculture to mitigate the effects of urbanization, including limited land availability, environmental degradation, and food deserts. It examines various urban farming practices, such as rooftop gardens, vertical farms, and community gardens, highlighting their benefits in promoting local food systems and enhancing community resilience. By analyzing case studies from various cities worldwide, the study evaluates the effectiveness of urban agriculture initiatives in improving food access, reducing carbon footprints, and fostering social cohesion. The findings underscore the importance of supportive policies and community engagement in maximizing the potential of urban agriculture. Ultimately, this article advocates for the integration of urban agriculture into urban planning as a sustainable approach to meet the food needs of growing urban populations.